Pengaruh Lingkungan Sekolah Terhadap Motivasi Belajar Siswa SMP N 3 Tarutung - Glorya Simanjuntak; Ruslan Juliana Pardosi; Robinhot Sihombing (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of the school environment on the learning motivation of students at SMP Negeri 3 Tarutung in the 2025/2026 academic year. The method used in this research is an inferential quantitative research method. The population in this study consisted of all students of SMP Negeri 3 Tarutung in the 2025/2026 academic year, totaling 655 students. In this study, the sample size was determined to be 66 students using the stratified random sampling technique. Data were collected using a closed questionnaire consisting of 48 items. The results of the data analysis indicate that there is an influence of the school environment on students’ learning motivation at SMP Negeri 3 Tarutung amounting to 45.2%. These results can be proven through the research findings: (1) analysis prerequisite tests: (a) the normality test result = 0.54 > 0.05, indicating that the research data are normally distributed; (b) the linearity test = 0.132 > 0.05, indicating that there is a significant linear relationship between the two variables. (2) Hypothesis testing: (a) the correlation coefficient test obtained a value of rxy = 0.637 > 0.239, indicating that there is a positive relationship between variable X and variable Y; (b) the significance test of the correlation coefficient obtained a value of tcount = 7.270 > ttable = 1.669, indicating that there is a significant relationship between variable X and variable Y. Therefore, Ha is accepted and H0 is rejected. (3) The regression coefficient of determination test (r²) = 45.2%. Thus, the results of the study show that 45.2% of the school environment influences the learning motivation of students at SMP Negeri 3 Tarutung in the 2025/2026 academic year.